Prospective study to estimate the role of different infertility factors in prediction of unsuccessful IVF outcome - V.O. Berestovyi; A. Mahmood; A.M. Martych; A.B. Prylutska; O.O. Berestovyi; D.O. Govsieiev (Publishing House TRILIST, 2021)
Research objective: in a prospective controlled study to investigate the role of HSP60, GroEl and other infertility factors as predictors of successful IVF outcome. Materials and methods. 106 female patients were divided into two groups: 54 individuals who received conventional treatment for infertility (using ICSI techniques for IVF) and 52 individuals who received conventional therapy with intravenous IgG, enoxaparin and aspirin. All collected blood samples were tested for HSP60 and GroEl antibodies using immunofluorescence and ELISA techniques at the time of admission, after treatment (and before embryo transfer), and after embryo transfer. We analyzed the factors that can be helpful as prognostic parameters to estimate the risk of implantation failure. Results. The risk of implantation failure is predicted when HSP60 level decreases from the first to the second measurement by less than 0.02 optical density units, with a sensitivity of 62% (95% confidence interval (CI) 47.2-75.3), and a specificity of 87.5% (95% CI 75.9-94.8), the positive predictive value was 81.6% (95% CI 68.2-90.2), the negative predictive value was 72.1% (95% CI 64.1-78.8). The GroEl value for the second dimension was more than 0.411 optical density units, which suggests a risk of treatment failure with a sensitivity of 64% (95% CI 49.2-77.1) and a specificity of 85.6% (95% CI 73.8-93.6), the positive predictive value was 80.0% (95% CI 67.1-88.7), the negative predictive value was 72.7% (95% CI 64.5-79.7). The highest (p < 0.05) value was observed at the beginning of treatment, and the lowest (p < 0.05) - during the third measurement. Treatment of the underlying cause of infertility led to a decrease in HSP60 and GroEl levels, which ensured a positive in vitro fertilization result. It was found that HSP60 and GroEl have a strong association with embryo implantation. The risk of implantation failure was strongly associated with twelve factors, the area under the curve (AUC) was 0.85 (95% CI 0.76-0.91). Conclusions. HSP60 and GroEl are good prognostic factors for predicting a successful IVF outcome in patients undergoing infertility treatment. The measurement of these parameters during the initial infertility examination may help in the immediate diagnosis of autoimmune infertility. Embryo implantation is a multifactorial process. The risk of implantation failure should be evaluated with multiple factors (twelve factors).